2018
DOI: 10.3390/rs10030477
|View full text |Cite
|
Sign up to set email alerts
|

Climate Extremes and Their Impacts on Interannual Vegetation Variabilities: A Case Study in Hubei Province of Central China

Abstract: As the frequency and intensity of climate extremes are likely to be substantially modified in upcoming decades due to climate warming, an evaluation of the response of interannual vegetation variabilities to climate extremes is imperative. This study comprehensively analyzed the spatio-temporal variabilities of 21 temperature and precipitation indices across Hubei Province in Central China based on daily meteorological records for the period 1961-2015. To quantify the sensitivity of the vegetation to climate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…In terms of temporal variation pattern, the main warm indices of meteorological stations in the Yangtze River Basin showed an upward trend, while the cold indices showed a downward trend, which is not only consistent with the previous research results in the same region, but is also in good agreement with that reported in Loess Plateau, China, Central Asia, Europe, and globally [47]. Spatially, the main warm indices also presented an increasing tendency, while the cold indices a decreasing tendency, which is consistent with the previous research results in the same region, and also in accordance with many studies in other regions [54]. The main cold indices changed abruptly in the 1980s and the main warm indices changed abruptly in the late 1990s and early 2000s, which is similar to the results of other scholars.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…In terms of temporal variation pattern, the main warm indices of meteorological stations in the Yangtze River Basin showed an upward trend, while the cold indices showed a downward trend, which is not only consistent with the previous research results in the same region, but is also in good agreement with that reported in Loess Plateau, China, Central Asia, Europe, and globally [47]. Spatially, the main warm indices also presented an increasing tendency, while the cold indices a decreasing tendency, which is consistent with the previous research results in the same region, and also in accordance with many studies in other regions [54]. The main cold indices changed abruptly in the 1980s and the main warm indices changed abruptly in the late 1990s and early 2000s, which is similar to the results of other scholars.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…Hubei Province is located in Central China (between 29 °01′ and 33 °06′ north latitude and between 108 °21′ and 116 °07′ east longitude), and it has an area of approximately 185,900 km 2 (Figure 1) (Wang et al, 2014;Chen et al, 2018). The terrain of Hubei is higher in the west and lower in the middle and includes various and complicated geomorphic types, such as mountains, hills, and plains, among which mountains account for approximately 55%, hills account for 24.5%, and plains account only for 20% of the total area.…”
Section: Study Areamentioning
confidence: 99%
“…where AI represents the vegetation vulnerability under drought stress, x n represents the environmental variables, β n represents standard regression coefficients, and ε represents the constant of the regression model. In the multiple regression model, the p-value for an F-test determines the addition and removal of terms [62]. For an MLR, all the variables were chosen to model the correlation between AI and environmental factors.…”
Section: Multivariate Linear Regression (Mlr)mentioning
confidence: 99%